PENGEMBANGAN APLIKASI BIBLIOFIL BERBASIS METODE SURVEY, QUESTION, READ, REFLECT, RECITE, REVIEW (SQ4R) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN TEKS DESKRIPSI SISWA KELAS V SEKOLAH DASAR - Irawan, Dea Febrina; Ani Hendriani; Dwi Heryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low level of students' reading comprehension skills. This condition is reflected in the achievement of students' knowledge, attitudes, and skills that have not met the expected standards, so that development efforts are needed. One solution offered is the innovation of interactive learning media that can support the improvement of students' reading comprehension skills. This study aims to develop a Bibliofil application based on the SQ4R method as a means to improve the reading comprehension skills of 5th grade students. The type of research used is design and development (DnD) with the ADDIE model developed by Dick and Carey (1996), which includes five stages: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. Data collection techniques include pre-research: observation, work logs and questionnaires, and during the research: tests and non-tests, with data analysis using qualitative and quantitative descriptive approaches. The results of the study indicate that the Bibliofil application was successfully developed by integrating learning objectives and reading comprehension indicators, and activities in the application are aligned with the steps of the SQ4R method. Based on expert validation, the application received an average score in the excellent category. Product implementation demonstrated improved learning outcomes with a high N-Gain rating for knowledge, moderate for attitudes, and excellent for skills. Therefore, it can be concluded that the Bibliofil application is effective in improving students' reading comprehension skills.